2021
DOI: 10.1155/2021/5525398
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Antipsychotic Medications with Low-Dose Clozapine in Treatment-Resistant Schizophrenia—Case Reports and Discussion

Abstract: Treatment resistance in schizophrenia is often encountered in clinical practice, with clozapine usually recommended as the appropriate therapy. However, where clozapine proves ineffective or cannot be tolerated due to side effects, treatment options are limited. In patients within forensic mental health services, residual symptomatology often presents a barrier to discharge and can have lasting effects on prospects for rehabilitation as well as risk to self and others. This paper presents a review of the relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Duration of follow up varied from 3 months 14 to 3 years 21 and it was not reported in three study 16,19,24 and not applicable in one study 18 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Duration of follow up varied from 3 months 14 to 3 years 21 and it was not reported in three study 16,19,24 and not applicable in one study 18 …”
Section: Resultsmentioning
confidence: 99%
“…Duration of follow up varied from 3 months 14 to 3 years 21 and it was not reported in three study 16,19,24 and not applicable in one study. 18 With regards to side effects, Bioque et al 20 reported that the combination of clozapine with LAI resulted in fewer side effects and was well tolerated.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…There are earlier reports of augmentation of antipsychotics with low-dose clozapine in the management of TRS. 4 Hence, clozapine was added to aripiprazole at the dose of 12.5 mg/d and gradually up-titrated to 75 mg/d over 2 weeks. The improvement in the positive symptoms was noted within a week of adding clozapine.…”
Section: Management Of Treatment-resistant Schizophrenia In a Patient...mentioning
confidence: 99%
“…We did not consider monotherapy of clozapine considering the following: partial response with aripiprazole, clozapine associated seizures are dose-dependent and that monotherapy would have necessitated a higher dose of clozapine, which could have increased the risk of seizures further. There are earlier reports of augmentation of antipsychotics with low-dose clozapine in the management of TRS 4 . Hence, clozapine was added to aripiprazole at the dose of 12.5 mg/d and gradually up-titrated to 75 mg/d over 2 weeks.…”
mentioning
confidence: 99%